(R)-α-lipoic acid oral liquid formulation: pharmacokinetic parameters and therapeutic efficacy - Brufani, Mario; Figliola, Rocco (Acta Biomedica Atenei Parmensis, 2014)
Despite its numerous potentials, oral administration of α-lipoic acid (ALA) is characterised by pharmacokinetic limitations that reduce its therapeutic efficacy. Indeed, phenomena such as reduced solubility, lack of gastric stability and hepatic degradation determine a bioavailability of around 30% and a short half-life of ALA. The innovative oral formulation has the potential to overcome these pharmacokinetic limitations as it uses only the R enantiomer of α-lipoic acid, the natural and more active form, whose solubility and stability in gastric environment are ensured by the patented liquid solution. Analysis of the pharmacokinetic profile showed that, with this formulation, the absorption of R-ALA is accelerated with high plasmatic concentrations and prolonged stability. Therefore, the bioavailability, which tends towards intravenous bioavailability, is markedly greater than that recorded with a solid R-ALA formulation. To overcome the pharmacokinetic limitations of current solid oral formulations, one potentiates the biological efficacy of ALA: indeed, in animal models, R-ALA in a liquid formulation amplifies the recovery of the conduction velocity of sensory and motor nerves altered by diabetic neuropathy. These results highlight that the characteristics of R-ALA in the liquid formulation lead to a more effective and faster biological response suggesting a new therapeutic scenario for numerous oxidative stress-dependent pathologies (diabetic complications, peripheral neuropathies, neurodegenerative and cardiovascular diseases, etc.) requiring chronic treatment.